2010
DOI: 10.1111/j.1463-1318.2009.01814.x
|View full text |Cite
|
Sign up to set email alerts
|

Streptococcus bovis endocarditis, a silent sign for colonic tumour

Abstract: Streptococcus bovis endocarditis and/or bacteraemia is an early clue to the likely presence of colorectal cancer. Whilst further studies are required to determine the precise pathophysiology, clinicians should be aware of this association. It is advisable to investigate rigorously for colon cancer in all patients presenting with S. bovis endocarditis/bacteraemia; such patients may also present with liver disease or, occasionally, extra-colonic malignancy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
87
0
5

Year Published

2012
2012
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 127 publications
(95 citation statements)
references
References 51 publications
3
87
0
5
Order By: Relevance
“…Moreover, recurrent infections may occur in both CRC and aplastic anemia. Streptoccocusbovis septicemia is classically associated with colorectal cancer [11] ; other organisms include Enterobacter [12] and Clostridium species [13] . Infections that are seen in aplastic anemia also include Streptoccocus and Clostridium species, in addition to Escherichia coli and others [14] .…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, recurrent infections may occur in both CRC and aplastic anemia. Streptoccocusbovis septicemia is classically associated with colorectal cancer [11] ; other organisms include Enterobacter [12] and Clostridium species [13] . Infections that are seen in aplastic anemia also include Streptoccocus and Clostridium species, in addition to Escherichia coli and others [14] .…”
Section: Discussionmentioning
confidence: 99%
“…The remarkable association between adenomatous polyps and S. bovis/gallolyticus seems to be of importance due to the compelling evidence that colon cancer progresses from normal tissue to adenoma and then to carcinoma through an accumulation of genetic alterations (Baron & Sandler, 2000). Although ulceration of the neoplastic lesion might form a pathway for the S. bovis/gallolyticus to enter the bloodstream (Gupta et al, 2009), the association of S. bovis/gallolyticus bacteremia with non-ulcerated colonic polyps indicates an etiological/promoter role of these bacteria in polyps progression (Cutait et al, 1988;Konda & Duffy, 2008). The possibility of S. bovis/gallolyticus to act as a promoter for the preneoplastic lesions is worthy to be considered.…”
Section: The Association Of Premalignant Colorectal Lesions With S Bmentioning
confidence: 99%
“…However, the extent, nature, and basis of this association are still not completely understood. S. bovis/gallolyticus became important in human health since it was shown that 25 to 80% of patients who presented S. bovis/gallolyticus bacteremia had also a colorectal tumor and the incidence of association of colonic neoplasia with S. bovis/gallolyticus endocaditis was shown to be 18 to 62% (Gupta et al, 2009;Kok et al, 2007;Leport et al, 1987;Malkin et al, 2008;Murray & Roberts, 1978;Reynolds et al, 1983;Wilson et al, 1981;Zarkin et al, 1990). The knowledge that there is an association between endocarditis from S. bovis/gallolyticus and carcinoma of the colon has important clinical implications (Boleij et al, 2009a;Kok et al, 2007).…”
Section: The Association Of Colorectal Cancer With S Bovis/gallolytimentioning
confidence: 99%
See 2 more Smart Citations